2018
DOI: 10.7554/elife.30391
|View full text |Cite
|
Sign up to set email alerts
|

CtBP impedes JNK- and Upd/STAT-driven cell fate misspecifications in regenerating Drosophila imaginal discs

Abstract: Regeneration following tissue damage often necessitates a mechanism for cellular re-programming, so that surviving cells can give rise to all cell types originally found in the damaged tissue. This process, if unchecked, can also generate cell types that are inappropriate for a given location. We conducted a screen for genes that negatively regulate the frequency of notum-to-wing transformations following genetic ablation and regeneration of the wing pouch, from which we identified mutations in the transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 84 publications
4
49
1
Order By: Relevance
“…Previously, while characterizing the role of CtBP in regulating regenerative plasticity, our group reported that loss of CtBP function results in the upregulation of several reporters of AP-1 activity (Worley et al, 2018), suggesting that JNK and CtBP may have opposing effects on shared transcriptional targets (Figure 5A). Since we have demonstrated the minimal ban enhancer is activated by JNK signaling, we hypothesized that CtBP may normally antagonize this effect, which could explain why brC12-lacZ expression is increased in CtBP mutant tissue.…”
Section: Ctbp Also Regulates Brc12 Activity By Antagonizing Jnk Signamentioning
confidence: 93%
See 1 more Smart Citation
“…Previously, while characterizing the role of CtBP in regulating regenerative plasticity, our group reported that loss of CtBP function results in the upregulation of several reporters of AP-1 activity (Worley et al, 2018), suggesting that JNK and CtBP may have opposing effects on shared transcriptional targets (Figure 5A). Since we have demonstrated the minimal ban enhancer is activated by JNK signaling, we hypothesized that CtBP may normally antagonize this effect, which could explain why brC12-lacZ expression is increased in CtBP mutant tissue.…”
Section: Ctbp Also Regulates Brc12 Activity By Antagonizing Jnk Signamentioning
confidence: 93%
“…We had previously identified CtBP, which encodes a transcriptional corepressor, in a screen for genes that regulate regenerative plasticity (Worley et al, 2018). In a separate screen, we identified an allele of CtBP as a mutation that enables mutant cells to outgrow their wild-type neighbors.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence was then beginning to accumulate that apoptosis can cause cells to change their identity before they expire (Szabad, Simpson, & Nöthiger, ), and the case has grown stronger since then (Worley, Alexander, & Hariharan, ), so Meinhardt simply connected all of these dots: (a) the mutation causes curved zones of cell death (Figure b), (b) the cells in such an A zone could switch identity from A to P, in which case (c) a thick arc of P cells might now overlap the AD/AV boundary (Figure c), and if so, then (d) two new AD/AV/P intersection points would ensue, and (e) two new legs would branch out (Figure d). He explained that the legs are mirror symmetric because the clockwise or counterclockwise (P→AV→AD) order of the areas around the intersection point would dictate each leg's handedness.…”
Section: The Boundary Modelmentioning
confidence: 99%
“…Evidence was then beginning to accumulate that apoptosis can cause cells to change their identity before they expire (Szabad, Simpson, & Nöthiger, 1979), and the case has grown stronger since then (Worley, Alexander, & Hariharan, 2018), so Meinhardt simply connected all of these dots: (a) the mutation causes curved zones of cell death ( Figure 6b Despite the elegance of Meinhardt's model, it lacked enough supporting evidence to be widely accepted at the time (Marsh & Theisen, 1999). Nevertheless, its fortunes were about to change.…”
Section: The Boundary Modelmentioning
confidence: 99%
See 1 more Smart Citation